Assistance in Strengthening Tourism Communication Skills in The Coban Goa Jalmo Tourism Awareness Group, Cendono Village, Pasuruan Regency - Hesty Octafiani; Zainul Ahwan (LPPM Universitas Yudharta Pasuruan, 2022)
The limited knowledge and skills of the poor in orphanages cause problems of their economic independence. To minimize this problem, community service programs are implemented to empower the poor through entrepreneurship training and home-scale industry assistance. The approach method used is entrepreneurship training and assistance in the manufacture of seasonings in packaging that are selling value. The results of the training and mentoring in the manufacture of packaged spices include the product of four kinds of spices in packaged bottles, namely rawon, empal, red chili and green chili sauce. Entrepreneurship training and business planning are carried out in several activities including entrepreneurship motivation, recording business activities, making business plans, and calculating profits and losses in business. The implementation of the program can be carried out well because of the intensive assistance and cooperation between the orphanage as partner 1 and partner 2 in accommodating and marketing the home-scale industrial products fostered by the Mawaddah Warohmah orphanage.